Hubungan Tingkat Aktivitas Fisik Dengan Kekambuhan Rheumatoid Arthritis di RSUD Sawah Besar Jakarta Pusat - Marsella, Marsella; Mustafida, Ika; Juliani, Enni (Pustaka Galeri Mandiri, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes inflammation in the body, particularly in the joints. According to data from the Global Burden of Diseases, Injuries, and Risk Factors Study in 2020, approximately 17.6 million people worldwide live with RA. In the service area of Sawah Besar General Hospital, there were 21 cases of RA in 2025. This is attributed to factors such as genetics, hormones, neuroendocrine conditions, and comorbidities that can trigger RA. Preliminary studies indicate that most patients continue to engage in heavy physical activities, which may contribute to RA flare-ups. This study aims to investigate the relationship between physical activity levels and RA flare-ups at RSUD Sawah Besar in Central Jakarta in 2025. This study used a quantitative method with a cross-sectional design, and the sample consisted of 21 respondents selected through non-probability sampling using the total sampling method. The research instruments used were questionnaires on physical activity levels (GPAQ) and RA relapses. Data were analyzed using univariate and bivariate methods with the Spearman rho test. The results of this study indicate that the majority of respondents had a high level of physical activity (76.19%) and frequent RA recurrence (52.4%). The Spearman's rho test results showed a very strong and significant correlation between the two variables